Sol-Gel Deposited Electrochromic Films for Electrochromic Smart Window Glass - Nilgün Özer; Carl M Lampert; Michael D. Rubin (International Symposium on Glass Problems, International Commission on Glass, 1996)
Electrochrornic windows offer the ability to dynamically change the transmittance of a glazing. With the appropriate sensor and controls, this smart window can be used for energy regulation and glare control for a variety of glazing applications. The most promising are building and automotive applications. This work covers the use of sol-gel deposition processes to make active films for these windows. The sol-gel process offers a low-capital investment for the deposition of these active films. Sol-gel serves as an alternative to more expensive vacuum deposition processes. The sol-gel process utilizes solution coating followed by a hydrolysis and condensation. In this investigation we report on tungsten oxide and nickel oxide films made by the sol-gel process for electrochromic windows. The properties of the sol-gel films compare favorably to those of films made by other techniques. A typical laminated electrochromic window consists of two glass sheets coated with transparent conductors, which are coated with the active films. The two sheets are laminated together with an ionically conductive polymer. The range of visible transmission modulation of the tungsten oxide was 60% and for the nickel oxide was 20%. We used the device configuration of glass/SnO2:F/WO3/polymer/LizNiOxHy/SnO2:F to test the films. The nickel oxide layer had a low level of lithiation and possibly contained a small amount of water. Lithiated oxymethylene-linked poly(ethylene oxide) was used as the laminating polymer. Commercially available Sn02:F/glass (LOF-Tec glass) was used as the transparent conducting glass. We found reasonable device switching characteristics which could be used for devices.